By honor bound : state and society in early modern Russia - Kollmann, Nancy Shields, 1950- (Cornell University Press, 1999)
"In the sixteenth and seventeenth centuries, Russians from all ranks of society were bound together by a culture of honor. In this book, one of the foremost scholars of early modern Russia explores the intricate and highly stylized codes that made up this culture. Drawing on a rich array of archival and published sources, Nancy Shields Kollmann describes how these codes were manipulated to construct identity and enforce social norms - and also to defend against insults, to pursue vendettas, and generally to unsettle communities. She offers compelling evidence for a new view of the relationship of state and society in the Russian empire, and her richly comparative approach enhances knowledge of statebuilding in premodern Europe."--